2011
DOI: 10.1124/jpet.111.185116
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two Mutations, M287L and Q266I, in the α1 Glycine Receptor Subunit That Modify Sensitivity to Alcohols

Abstract: Glycine receptors (GlyRs) are inhibitory ligand-gated ion channels. Ethanol potentiates glycine activation of the GlyR, and putative binding sites for alcohol are located in the transmembrane (TM) domains between and within subunits. To alter alcohol sensitivity of GlyR, we introduced two mutations in the GlyR ␣1 subunit, M287L (TM3) and Q266I (TM2). After expression in Xenopus laevis oocytes, both mutants showed a reduction in glycine sensitivity and glycine-induced maximal currents. Activation by taurine, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 41 publications
6
48
0
Order By: Relevance
“…In addition, the recent pharmacologic characterization of another GlyR a1 subunit mutant (M287L), also with decreased ethanol sensitivity, revealed that zinc did not enhance the effects of ethanol on mutant receptors at nanomolar concentrations that were sufficient for increasing ethanol potentiation at WT GlyRs (Borghese et al, 2012). This further indicates that zinc is crucial in determining the sensitivity of GlyRs to ethanol and highlights the importance of including zinc in studies of ethanol actions.…”
Section: Zinc and Ethanol Modulation Of Glycine Receptor Functionmentioning
confidence: 87%
“…In addition, the recent pharmacologic characterization of another GlyR a1 subunit mutant (M287L), also with decreased ethanol sensitivity, revealed that zinc did not enhance the effects of ethanol on mutant receptors at nanomolar concentrations that were sufficient for increasing ethanol potentiation at WT GlyRs (Borghese et al, 2012). This further indicates that zinc is crucial in determining the sensitivity of GlyRs to ethanol and highlights the importance of including zinc in studies of ethanol actions.…”
Section: Zinc and Ethanol Modulation Of Glycine Receptor Functionmentioning
confidence: 87%
“…Furthermore, labeling was facilitated by channel opening, consistent with an alcohol-binding cavity whose structure and/or accessibility is coupled to channel gating. Additional transmembrane residues, including M1 I229 (Lobo et al, 2008), M2 Q149, and M3 M287 (Borghese et al, 2012), and in the extracellular portion of M4 (Lobo et al, 2006),were also shown to influence alcohol and anesthetic modulation, suggesting these positions all contribute to a shared transmembrane binding cavity.…”
Section: A Eukaryotic Inhibitory Channelsmentioning
confidence: 99%
“…An important contribution of the approach is the ability to rule out potential targets. For example, the a1 subunit of the glycine receptor was considered one of the most likely mediators of spinal immobility produced by inhaled anesthetics (Eger et al, 2008), but this was shown not to be the case through use of knock-in mice (Borghese et al, 2012). A different approach was taken for nicotinic receptors, where gain of function was engineered into specific receptor subunits in mice (Drenan and Lester, 2012).…”
Section: A Behavioral Pharmacology In Rodent Modelsmentioning
confidence: 99%
“…Two separate gene-targeting experiments were conducted to create two independent GlyR ␣1 subunit KI mouse lines harboring mutations that changed glutamine at position 266 to isoleucine (Q266I KI) or methionine at position 287 to leucine (M287L KI) (Borghese et al, 2012). All mice were derived from a 129S1/X1 ϫ C57BL/6J hybrid genetic background that was subsequently backcrossed to C57BL/6J for two generations at the University of Pittsburgh (Pittsburgh, PA).…”
Section: Methodsmentioning
confidence: 99%
“…Our recent studies of alcohol actions on recombinant GlyRs (Borghese et al, 2012) showed that mutations M287L in the transmembrane 3 region and Q266I in the transmembrane 2 region of the ␣1 subunit lead to a reduction in ethanol potentiation of glycine-induced current. Construction of knockin (KI) mice with each of these mutations allowed behavioral testing to determine the influence of these changes on behavioral effects of ethanol and other drugs.…”
Section: Introductionmentioning
confidence: 99%